Kondisi Akses Air Bersih dan Dampaknya terhadap Kesehatan Masyarakat : Studi Kasus di Desa Swadaya (Inovasi Kesehatan Global, 2026)
This study aims to describe the condition of clean water access and its impact on public health in Swadaya Village. The research employed a qualitative approach through in-depth interviews with household heads, community leaders, health workers, and local water managers. The findings reveal that access to clean water in Swadaya Village remains very limited. Most residents rely on dug wells and river water for daily needs, while only a small portion use water from the local water utility (PDAM) due to high installation costs and limited pipeline coverage. The water quality often decreases during the dry season, becoming cloudy, odorous, and causing skin irritation. These conditions contribute to the increasing incidence of waterborne diseases such as skin infections, diarrhea, and typhoid fever. Besides infrastructure limitations, the lack of community awareness regarding hygiene and sanitation practices worsens the situation. Although the village government has proposed clean water development programs, their implementation has been hampered by budget constraints. The study concludes that clean water problems in Swadaya Village are not only related to resource availability but also to environmental management and community behavior. Therefore, improving water infrastructure must be accompanied by community education to promote a healthy, safe, and sustainable living environment.